Pelatihan Pembuatan Pupuk Organik Melalui Pengolahan Limbah Rumah Tangga - M. Maulana Asegaf; Mochammad Ilyas Junjunan; M. Alfan Nashrullah; Ali Ridho Syafi'i; Hafshah Rauliah Alfani (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Waste is a problem that is being experienced by all humans in this modern era. Waste is the root of the problem of environmental damage and global warming. It is necessary to do a way of handling and processing waste so that environmental damage can be prevented. Senggowar Village in Nganjuk Regency can also play a role in treating waste that exist in the community. With the majority of people as farmers, organic fertilizer processing from household waste is the right choice. Therefore, training is carried out to the community so that they can understand how to make processed organic waste into organic fertilizer.